Ultrasound technology for food fermentation applications - Ojha, K. Shikha; Mason, Timothy J.; O’Donnell, Colm P.; Kerry, Joseph P.; Tiwari, Brijesh K. (Ultrasonics sonochemistry, 2017)
•High frequency ultrasound for monitoring of fermentation process.•Low frequency ultrasound can enhance fermentation rates.•Ultrasound can accelerate microbial growth rates. Fermentation processes involve the participation of enzymes and organic catalysts, generated by range of microorganisms to produce chemical transformations. Ultrasound can be used in such processes to either monitor the progress of fermentation or to influence its progress. High frequency ultrasound (>2MHz) has been extensively reported as a tool for the measurement of the changes in chemical composition during fermentation providing real time information on reaction progress. Low frequency ultrasound (20–50kHz) can influence the course of fermentation by improving mass transfer and cell permeability leading to improved process efficiency and production rates. It can also be used to eliminate micro-organisms which might otherwise hinder the process. This review summarises key applications of high and low frequency ultrasound in food fermentation applications.